Neuronopathic Types of Mucopolysaccharidoses: Pathogenesis and Emerging Treatments - L. A. Osipova; L. M. Kuzenkova; L. S. Namazova-Baranova; A. K. Gevorkyan; T. V. Podkletnova; N. D. Vashakmadze (Вопросы современной педиатрии)
Mucopolysaccharidoses are a group of hereditary metabolic diseases, relating to lysosomal storage disorders and caused by a deficiencyof the enzymes, involved in degradation of glycosaminoglycans (mucopolysaccharides). Severe forms of mucopolysaccharidoses of types I, II and VII and mucopolysaccharidosis of type III are characterised by primary central nervous system damage and neurodegenerative course of the disease with cognitive decline, behavioural abnormalities and decreased lifespan. Neuropathogenesis of mucopolysaccharidoses is not completely studied. The question of reversibility of cellular damage is still open. There is currently no effective treatment for mucopolysaccharidoses with primary central nervous system damage. Intravenous enzyme replacement therapy doesn’t cross the blood-brain barrier and has no influence on neurodegeneration. Investigation of alternative treatment options, providing delivery of therapeutic agent to central nervous system, is currently being carried out. Preclinical studies of highdose, intrathecal, intraventricular enzyme replacement therapy; administration of modified enzyme, capable of crossing the blood-brain barrier; gene, cell therapies, stop codon readthrough approach and substrate reduction therapy show promising results.